Effects of ZSET1446/ST101 on Cognitive Deficits and Amyloid β Deposition in the Senescence Accelerated Prone Mouse Brain - Yoshimasa Yamaguchi; Kenichi Saito; Toshiyuki Matsuno; Kentaro Takeda; Masataka Hino (Elsevier, 2012)
The senescence accelerated prone mouse strain 8 (SAMP8) develops age-related deficits in learning and memory. Effects of the azaindolizinone derivative ZSET1446/ST101, a newly synthesized cognitive enhancer, on cognitive impairment and deposition of amyloid β (Aβ) were assessed in the SAMP8. ZSET1446 was administered in drinking water at estimated doses of 0.002, 0.01, and 0.1 mg/kg per day from the age of 8 months. The SAMP8 at the age of 8 months showed cognitive impairment in a novel object recognition task compared with young SAMP8 at the age of 8 weeks. Further, grading scores were gradually increased from 9 to 12 months and Aβ-like immunoreactivity in the hippocampus was increased at the age of 10 months. ZSET1446 ameliorated cognitive deficits of SAMP8 after 4, 8, 12, and 16 weeks of treatment in a novel object recognition test. ZSET1446 also reduced grading scores of SAMP8 after 16 weeks of treatment. Further, 8-week treatment of ZSET1446 significantly reduced the total number of Aβ-positive granules in the hippocampus. These results suggest that ZSET1446 shows ameliorating effects on SAMP8 partly due to the suppression of an increase of Aβ-deposition in the hippocampus. Keywords:: ZSET1446, senescence accelerated prone mouse strain 8 (SAMP8), object recognition test, amyloid β, grading score